2021
DOI: 10.3390/metabo11090584
|View full text |Cite
|
Sign up to set email alerts
|

Tolerant Larvae and Sensitive Juveniles: Integrating Metabolomics and Whole-Organism Responses to Define Life-Stage Specific Sensitivity to Ocean Acidification in the American Lobster

Abstract: Bentho-pelagic life cycles are the dominant reproductive strategy in marine invertebrates, providing great dispersal ability, access to different resources, and the opportunity to settle in suitable habitats upon the trigger of environmental cues at key developmental moments. However, free-dispersing larvae can be highly sensitive to environmental changes. Among these, the magnitude and the occurrence of elevated carbon dioxide (CO2) concentrations in oceanic habitats is predicted to exacerbate over the next d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 102 publications
(165 reference statements)
1
14
1
Order By: Relevance
“…Conversely, a study on H. americanus found a positive correlation between elevated pCO 2 and carapace and abdomen length (Menu-Courey et al, 2019). We believe the effects on size observed in our study are not as strong as the study by Menu-Courey et al (2019) and Noisette et al (2021) possibly because the pCO 2 gradient treatments used in those studies reached higher concentrations (1200, 2000 and 3000 µatm) than ours. Furthermore, our study only focused on larval stages and decapod larvae exoskeletons are unmineralized while those of benthic juveniles are partially calcified (Anger, 2001).…”
Section: Size and Morphologycontrasting
confidence: 91%
See 2 more Smart Citations
“…Conversely, a study on H. americanus found a positive correlation between elevated pCO 2 and carapace and abdomen length (Menu-Courey et al, 2019). We believe the effects on size observed in our study are not as strong as the study by Menu-Courey et al (2019) and Noisette et al (2021) possibly because the pCO 2 gradient treatments used in those studies reached higher concentrations (1200, 2000 and 3000 µatm) than ours. Furthermore, our study only focused on larval stages and decapod larvae exoskeletons are unmineralized while those of benthic juveniles are partially calcified (Anger, 2001).…”
Section: Size and Morphologycontrasting
confidence: 91%
“…In the wild, this could translate to an additional obstacle for successful recruitment. Similarly, reduced survival due to elevated p CO 2 has been observed in early life stages in the European lobster ( Small et al, 2016 ) and in the congeneric American lobster ( Menu-Courey et al, 2019 ; Noisette et al, 2021 ). Moreover, this increase in mortality in early life stages of crustaceans exposed to ocean acidification has been noted in several other species: e.g.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…With the data currently available we are cautiously optimistic that snow crab are likely to prove resilient in the face of changing oceanic carbonate chemistry. Future work, however, should still be conducted as different life-history stages may respond very differently to OA; larval American lobsters ( Homarus americanus) are highly resilient whereas juveniles are very sensitive [67] and European lobster ( Homarus gammarus ) have both sensitive and resilient larval stages and a very sensitive juvenile stage [68,69]. Thus, studies examining all larval stages as well the juveniles stage of snow crab should be performed before it can be concluded that the species as a whole will be resistant to OA.…”
Section: Discussionmentioning
confidence: 99%
“…Many decapod species can, to some extent, compensate for CO2driven acidification of extracellular fluids by possessing effective mechanisms of acid-base regulation. Despite the apparent acid-base coping mechanisms, an individual's physiological development, life stage specificity and the ecological shifts it experiences can all contribute to the adaptation strategies for number of reasons: physiological capacity is still in development; larval exposure could carry negative impact for the subsequent stages making juveniles less tolerant (sensu Walther et al, 2010); loss of physiological control through the juvenile organogenesis requiring high energy expenditure (Noisette et al, 2021), or it may be that possessing such an ability as a larvae is not so critical given the habitats they occupy (although see Bednaršek et al, 2020). The exposure to hypercapnia may alter the swimming behavior of crab larvae, which is species-and life stage-dependent; while there was no effect of hypercapnia on stage V of the stone crab larvae, earlier life stage changes to faster downwards swimming, possibly affecting larval transport in increasingly hypercapnic sea water (Gravinese et al, 2019).…”
Section: Role Of Adaptation and Acclimatizationmentioning
confidence: 99%